PD-1 blockade and radiotherapy combination for advanced Epstein-Barr virus-associated intrahepatic cholangiocarcinoma: a case report and literature review - Liao, Chun-Xu; Deng, Chang-Song; Liang, Xia; Yang, Jian-Chuan; Chen, Zhi-Zhong; Lin, Xiao-Ying; Lin, Cai-Feng; Chen, Shen; Wu, Song-Song (Frontiers in Immunology, 2023)
Advanced intrahepatic cholangiocarcinoma (ICC) is a rare malignant tumor of biliary epithelial cells, known for its extremely unfavorable prognosis. In the absence of intervention, patients typically survive for less than 5 months. Current guidelines from the Chinese Society of Clinical Oncology (CSCO), National Comprehensive Cancer Network (NCCN), and European Society for Medical Oncology (ESMO) recommend chemotherapy-based systemic therapy as the standard treatment for advanced ICC. However, the first-line regimen, consisting of gemcitabine in combination with cisplatin, generally results in a median survival of approximately one year, which is considered suboptimal. Significant progress has been made in radiotherapy techniques, molecular diagnostics, and tumor immune microenvironments. The integration of immune and radiation therapies has revolutionized treatment strategies for cholangiocarcinoma. Moreover, combined therapeutic regimens have shown promising results in improving survival rates among patients with advanced ICC. In this study, we present a case report of a 70-year-old male patient diagnosed with stage IV ICC, featuring metastases to the retroperitoneal, left adrenal, and left supraclavicular lymph nodes. The patient exhibited a high tumor mutational load, significant microsatellite instability, and hyper-expression of PD-L1 (90%), along with positive Epstein-Barr virus-encoded RNA (EBER).Pembrolizumab, a programmed cell death 1 (PD-1) inhibitor, was administered in conjunction with radiotherapy. As a result, considerable shrinkage and inactivation of the primary foci were observed, accompanied by the disappearance of metastases. Ultimately, the patient achieved complete remission and maintained progression-free survival for 41 months following the initial treatment.To the best of our knowledge, this represents the longest case of complete remission using a combination of immunotherapy and radiotherapy as a first-line regimen for the high tumor mutational load, microsatellite instability, and PD-L1 expression (90%) subtype of Epstein-Barr virus-associated ICC (EBVaICC). These findings suggest that the combination of PD-1 inhibitors with radiotherapy may serve as a promising therapeutic strategy for treating this particular cancer subtype.